Using an Integrated Knowledge Translation (IKT) Approach to Enable Policy Change - Liddy, Clare; Moroz, Isabella; Joschko, Justin; Horsley, Tanya; Kuziemsky, Craig; Kovacs Burns, Katharina; Kossey, Sandi; Mitera, Gunita; Keely, Erin (Université d'Ottawa | University of Ottawa, 2018)
This paper explores our efforts to support the expansion of a regional electronic consultation (eConsult) service on a national level by addressing potential policy barriers. We used an IKT strategy based on five key activities leading to a National eConsult Policy Think Tank meeting: 1) identifying potential policy enablers and barriers, 2) engaging national and provincial/territorial partners, 3) including patient voices, 4) undertaking co-design and planning, and 5) adopting a solution-based approach. We successfully leveraged a diverse set of stakeholders in strategic discussions, culminating in actionable suggestions for next steps, which will serve to inform a national implementation strategy.